2019
DOI: 10.1039/c8nj05494k
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent fac-[Re(CO)3(phen)] carboxylato complexes with non-steroidal anti-inflammatory drugs: synthesis and mechanistic insights into the in vitro anticancer activity of fac-[Re(CO)3(phen)(aspirin)]

Abstract: Luminescent fac-[Re(CO)3(phen)(aspirin)]: insights into in vitro anticancer activity and confocal microscopy imaging in HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…An approximately 14 % increase in the sub‐G1 phase of HeLa cells was observed, which is a sign of pro‐apoptotic activity. Pro‐apoptotic activity of rhenium derivative 33 was further substantiated by the Annexin V and Caspase‐3/7 assay . Antiproliferative activity of 33 seems not to be directly linked to COX‐2 inhibition in the concentration range of 10 to 100 μM; the compound was not superior to the inhibitory activity of aspirin.…”
Section: Organometallic Acetylsalicylic Acid (Aspirin) Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…An approximately 14 % increase in the sub‐G1 phase of HeLa cells was observed, which is a sign of pro‐apoptotic activity. Pro‐apoptotic activity of rhenium derivative 33 was further substantiated by the Annexin V and Caspase‐3/7 assay . Antiproliferative activity of 33 seems not to be directly linked to COX‐2 inhibition in the concentration range of 10 to 100 μM; the compound was not superior to the inhibitory activity of aspirin.…”
Section: Organometallic Acetylsalicylic Acid (Aspirin) Derivativesmentioning
confidence: 99%
“…In 2019 Kowalski and co‐workers reported the synthesis and biological activity studies of fac ‐[Re(CO) 3 (phen)(aspirin)] complex 33 with phen=1,10‐phenanthroline (Figure ) . Compound 33 showed orange luminescence stemming from the metal‐to‐ligand charge‐transfer ( 3 MLCT) triplet excited state.…”
Section: Organometallic Acetylsalicylic Acid (Aspirin) Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and Dhar et al reported that a novel Pt(IV) prodrug of cisplatin, asplatin, with the ligation of aspirin ( c , c , t -[PtCl 2 (NH 3 ) 2 (OH) (aspirin)]), demonstrated significantly higher cytotoxicity than cisplatin towards tumor cells and nearly completely overcame the drug resistance of cisplatin-resistant cells [ 20 22 ]. Recently, Kowalski reported a new rhenium compound with AS as the ligand, fac -[Re(CO) 3 (phen)(aspirin)], which exhibited activity against HeLa human cancer cells, and this anticancer activity could be linked to ROS production, and cell cycle disturbance followed by triggering an apoptotic pathway of cell death [ 23 ]. Similar exciting antitumor effect has also been found in other metal-based complexes of SA.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination of NSAIDs to metal centers aims at obtaining antiproliferative activity through a dual mode of action: inhibition of COX and, e.g., ROS generation by the metal. Complexes of Ru II , Os II , Cu II , Re II , Fe II , Co II and Zn II with indomethacin, naproxen, diclofenac and ibuprofen have been reported [3][4][5][6][7][8][9][10][11]. Examples of ASA derivatives involve Ir III [12], Pt IV [13], Ag I [14,15] and various metal carbonyls [16][17][18].…”
Section: Introductionmentioning
confidence: 99%